Effective clearance of a persistent viral infection requires cooperation between virus-specific Lyt2+ T cells and nonspecific bone marrow-derived cells. - Jamieson, B D (1987)
The lifelong chronic lymphocytic choriomeningitis virus (LCMV) infection established in neonatally or congenitally infected mice can be eliminated by adoptive transfer of lymphoid cells from LCMV-immune mice. In this study, we have identified the effector cells mediating the clearance of persistent and disseminated LCMV infection. Using mice that are recombinant in the H-2 region and by selective depletion of lymphocyte subpopulations, we show that viral clearance was mediated by LCMV-specific Lyt2+ L3T4- T cells that are restricted to the class I genes of the major histocompatibility complex. In addition, our results show a requirement for host-derived bone marrow cells for the effective elimination of virus from the liver. These studies emphasize the importance of virus-specific T cells and an intact bone marrow function in viral clearance.